Some econometric evidence on the impact of the multifiber agreement on the German clothing industry - Joachim Zietz (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1985)
Since 1974, the year of the first Multi-fiber Agreement (MFA), a considerable number of studies has analyzed the economic impact of quotas such as those of the MFA on industrialized countries. Examples are the studies by Hamilton (1980), Morkre and Tarr (1980), Wolf et al. (1984), and GATT (1984), to name a few. Most of the work so far has relied either on models of the comparative static type, with reasonable parameters substituted, or on more ad hoc comparisons of pre- and post-MFA market shares or other similar indicators. However, there seems to be a dearth of econometric evidence, in particular for Germany. The present paper is intended to start filling this gap. Its purpose is to investigate the effect of the MFA quotas and MFA-induced voluntary export restraints (VERs) on the German clothing industry.
Keywords: 330